Clinical aspects of feline prostate cancer: a literature review - STANS, J (Journal of the Hellenic Veterinary Medical Society, 2021)
Feline prostate cancer is a rare condition, which means that the literature is very sparse. This makes it difficult to make sound conclusions about the epidemiology and the effectiveness of the treatment strategies that are utilized. The literature suggests that the condition mainly affects older cats and that these tumours are usually (adeno) carcinomas. Feline prostatic cancer patients often suffer from haematuria, dysuria and inappetence. Both surgery and chemotherapy have been used to treat the condition. Unfortunately, most animals still die within a year. Further research is needed to better understand the epidemiology of the disease and to guide treatment decisions.